Unions, Politics and Law in Canada - Neil, Michael (Relations industrielles / Industrial Relations, 1988)
This paper reviews some of the options that unions have followed in the past, and details some of the types of political activities in which unions can presently engage. The focus is on various legal constraints that may hinder union political activity.